PENGARUH FINANCIAL KNOWLEDGE, FINANCIAL ATTITUDE DAN SELF-CONTROL TERHADAP FINANCIAL MANAGEMENT BEHAVIOR PADA MAHASISWA PENERIMA KIP KULIAH UNIVERSITAS PGRI SEMARANG ANGKATAN 2021 - Dara Aprillia, Mandariska; Indriasari, Ika; Rr Hawik Ervina I (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
The purpose of this study is to determine how financial knowlede, financial attitude, self-control affect the financial management behavior of students who receive KIP Lecture at PGRI Semarang University in 2021. This research applies quantitative methods. The total sample taken was 142 students who received KIP Lecture at PGRI Semarang University from the Class of 2021. The sampling technique used was purposive sampling. To analyze the data, the software used is SPSS for Windows version 26. The findings of this study indicate that financial knowledge has no effect on financial management behavior on the contrary, both financial attitude and self-control have an influence on this behavior. The Summary Table reveals that the Adjusted value is 0.565 x 100% = 56.5%.